Development and validation of RP-HPLC method for determination of Duloxetine hydrochloride in bulk and dosage form - Bhimanadhuni, Chusena Narasimharaju; Garikapati, Devala Rao; Srinivas, Chintha (International Current Pharmaceutical Journal, 2012)
A reverse phase high performance liquid chromatographic method was developed for the determination of duloxetine hydrochloride in bulk and dosage form. The separation was effected on a kromasil ODS C18 column (250mmX4.6mm, 5?) using a mobile phase mixture of buffer and methanol in a ratio of 85:15 v/v at a flow rate of 1.0ml/min. The detection was made at 230nm. The retention time of duloxetine hydrochloride was found to be 3.443±0.06 min. Calibration curve was linear over the concentration range of 20-120?g/ml of duloxetine hydrochloride. The propose method was validated as per the ICH guidelines. The method was accurate, precise, specific and rapid found to be suitable for the quantitative analysis of the drug and dosage form. DOI: http://dx.doi.org/10.3329/icpj.v1i5.10281 International Current Pharmaceutical Journal 2012, 1(5): 98-102